2009
DOI: 10.1071/ea08276
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of heifer puberty in two tropical beef genotypes in northern Australia and associations with heifer- and steer-production traits

Abstract: Abstract.A total of 2115 heifers from two tropical genotypes (1007 Brahman and 1108 Tropical Composite) raised in four locations in northern Australia were ovarian-scanned every 4-6 weeks to determine the age at the first-observed corpus luteum (CL) and this was used to define the age at puberty for each heifer. Other traits recorded at each time of ovarian scanning were liveweight, fat depths and body condition score. Reproductive tract size was measured close to the start of the first joining period. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 43 publications
5
90
0
2
Order By: Relevance
“…In contrast to heritabilities of ,0.10 for most traditional reproductive traits, Johnston et al (2009) report that several pubertal traits such as age, weight and fat depth at time of first CL/CA were moderately to highly heritable (Table 2). In general, more genetic variation was observed for Brahmans than for Tropical Composites.…”
Section: Component Traits Of Female Reproductionmentioning
confidence: 91%
“…In contrast to heritabilities of ,0.10 for most traditional reproductive traits, Johnston et al (2009) report that several pubertal traits such as age, weight and fat depth at time of first CL/CA were moderately to highly heritable (Table 2). In general, more genetic variation was observed for Brahmans than for Tropical Composites.…”
Section: Component Traits Of Female Reproductionmentioning
confidence: 91%
“…In beef, Johnston et al (2009) reported indirect evidence of a negative genetic correlation (−0.6) between fertility (age at puberty) in heifers and RFI measured in their paternal half-brothers for Brahman, but not for Brahman crosses (where the genetic correlation is 0.02). Vallimont et al (2012) used a data set of 970 Holsteins and found unfavourable genetic correlations between RFI and three measures of fertility (daughter pregnancy rate, cow conception rate and heifer conception rate).…”
Section: Impact Of Selecting For Rfi On Other Traitsmentioning
confidence: 99%
“…Cattle were bred and supplied by the Cooperative Research Centre for Beef Genetic Technologies (Beef CRC) as described previously Johnston et al 2009). In brief, data from 1007 Brahman heifers and 1118 Brahman bulls were included in the current analysis.…”
Section: Cattle and Traitsmentioning
confidence: 99%
“…Puberty in heifers was defined by plasma progesterone concentration, ultrasound images of corpus luteum (CL) and detection of oestrous (Shamay et al 2005;Romano et al 2007;Johnston et al 2009). Puberty in bulls was defined by scrotal circumference thresholds and was related to sperm concentration, motility and morphology (Lunstra et al 1978;Bagu et al 2004;Siddiqui et al 2008;Corbet et al 2009).…”
Section: Introductionmentioning
confidence: 99%